2013
DOI: 10.1002/ange.201307097
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Dinitrogen‐Derived Hafnium Nitrides for Nucleophilic NC Bond Formation with a Terminal Isocyanate

Abstract: Anionenkoordination an einen verbrückten Hafnocen‐Nitrid‐Komplex, der durch CO‐induzierte N2‐Spaltung erhalten wurde, erhöht die Nucleophilie des N‐Atoms und fördert so eine zusätzliche N‐C‐Bindungsbildung mit einem typischerweise inerten terminalen Isocyanatliganden. Diese Kaskadensequenz ermöglicht die Synthese von sonst schwer zugänglichen, monosubstituierten Harnstoffen mithilfe von N2, CO und einem geeigneten Elektrophil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…While the hafnocene nitrides with 4-substituded pyridine donors were unreactive toward CO 2 , nitriles, and alkynes, 141 the parent pyridine derivative [{(η 5 142 Depending on the stoichiometry of the reaction, either [{(η 5 -…”
Section: Interaction Of N 2 With Transition Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the hafnocene nitrides with 4-substituded pyridine donors were unreactive toward CO 2 , nitriles, and alkynes, 141 the parent pyridine derivative [{(η 5 142 Depending on the stoichiometry of the reaction, either [{(η 5 -…”
Section: Interaction Of N 2 With Transition Metalsmentioning
confidence: 99%
“…While the hafnocene nitrides with 4-substituded pyridine donors were unreactive toward CO 2 , nitriles, and alkynes, the parent pyridine derivative [{(η 5 -C 5 H 2 -1,2,4-Me 3 ) 2 Hf} 2 ­(μ 2 ,η 2 ,η 2 -N 2 )]­(C 5 H 5 N) and the hafnocene without stabilizing donor [{(η 5 -C 5 H 2 -1,2,4-Me 3 ) 2 Hf} 2 ­(NCO)­(μ 2 -N)] share a more pronounced and diverse nitrogen functionalization chemistry. As shown in Scheme , addition of MeOTf to the pyridine stabilized complex [{(η 5 -C 5 H 2 -1,2,4-Me 3 ) 2 Hf} 2 ­(μ 2 ,η 2 ,η 2 -N 2 )]­(C 5 H 5 N) produced N–C bond formation between the isocyanate and the nitride ligand to the corresponding ureates [{(η 5 -C 5 H 2 -1,2,4-Me 3 ) 2 Hf} 2 ­(μ 2 -OTf)­(μ 2 -NCONX)] (X = H or Me) …”
Section: N–x Bond Formation With Retention Of the N–n Bondmentioning
confidence: 99%
“…6 More recently, Chirik reported that side-on bound N2 complexes can react with a wider range of reagents to form N-C bonds. [71][72][73][74] In the reaction described here, the distinctive feature is the partial reduction of N2 prior to its functionalization. This is valuable because it is not necessary for the metal-N2 complex to be particularly reactive; the N2 is rendered reactive through reduction/silylation.…”
Section: Mechanistic Evaluation Using Computationsmentioning
confidence: 99%
“…Direct conversion of N 2 into high-value N-containing organic compounds, not through NH 3 , is of great significance and challenging both fundamentally and practically . Although some progress in making C–N bonds through N 2 –transition metal or N 2 –actinide complexes and carbon-based reagents have been reported in the literature, such an approach is still in its infancy. As a class of important synthetic intermediates, hydrazine derivatives, which may contain up to four C–N bonds on the N–N single-bond skeleton, are primary targets for direct conversion of N 2 (Scheme ).…”
mentioning
confidence: 99%